Kinetic Modeling of Ethylene Oligomerization to High-Chain-Length Olefins Over Al-SBA-15-Supported Ni Catalyst with LiAlH4 Co-catalyst - Woo, Yesol; Shin, Mi; Suh, Young Woong; Park, Myung June (Reaction Kinetics, Mechanisms and Catalysis, 2021)
Kinetic modeling of ethylene oligomerization was performed; an Al-SBA-15-supported Ni catalyst and LiAlH4 co-catalyst were used to produce high-chain-length olefins in a one-pot reaction. A semi-batch slurry reactor produced kinetic data at different feed flow rates and temperatures. Grouping of the kinetic and mass transfer coefficients concerning the products was introduced to estimate undetermined parameters with limited experimental data. Among the four combinatorial cases, the estimation of individual kinetic parameters and grouped mass transfer coefficients showed the lowest errors and Akaike’s information criteria. The activation energies for the formation of hexene and octene were determined to be approximately 15 and 45 kJ/mol, respectively, confirming reported values of 23.1–64.1 kJ/mol. The model showed that the formation of short-chain-length olefins accounted for the rate-determining steps, and the evaluation for the effects of operating conditions guided optimal operation; high temperature and feed flow rate maximized heavy species production, and the flow rate should be optimized to maximize light olefin production.
Keywords: Ethylene oligomerizations; High temperature; Information criterion; Light olefin productions; Operating condition; Optimal operation; Rate determining step; Short chain lengths; Ethylene oligomerization; Heavy olefins; Kinetic modeling; Parameter estimation; Semi-batch slurry reactor